Ischemia-modified albumin, brain natriuretic peptide, and growth differentiation factor-15 levels in patients with nasal polyps - Sari, Kamran; Gencer, Zeliha Kapusuz; Ede, Huseyin; Gocmen, Ayse Yesim; Kantekin, Yunus (Auris, nasus, larynx, 2016)
Nasal polyps (NP) are a chronic inflammatory disease of the nasal mucosa; their etiology is suspected to involve oxidative stress. Growth differentiation factor-15 (GDF-15), brain natriuretic peptide (BNP), and ischemia-modified albumin (IMA) are biomarkers used especially in the early diagnosis and follow-up of cardiovascular diseases. The aim of this study was to assess levels of serum GDF-15, BNP, and IMA in patients with NP and to compare them with those of healthy subjects. This was a prospective study enrolling 41 patients with NP and 48 healthy controls, all aged 18–65 years and referred to the Department of Otorhinolaryngology, Head and Neck Surgery, between January 2014 and February 2015. After a 12-h fast, venous blood (3mL) was drawn and centrifuged (3000rpm, 10min) to collect serum. Blood samples were drawn before endoscopic sinus surgery in the NP group. Serum GDF-15, BNP, and IMA levels were measured. GDF-15, BNP, and IMA levels of patients with NP were statistically significantly higher than in controls and GDF-15 values were higher than the normal upper limit. GDF-15, BNP, and IMA levels were significantly correlated in both groups. As GDF-15 is a marker of chronic inflammation and oxidative stress, our finding of increased serum GDF-15 in patients with NP supports the hypothesis that its pathogenesis involves chronic inflammation and oxidative stress.